Perlindungan buruh migran Indonesia melalui deteksi dini HIV/AIDS pada saat reintegrasi ke daerah asal - Sri Endah Kinasih; Vinsensio M A Dugis (Masyarakat, Kebudayaan dan Politik, 2015)
As the number of Indonesian Migrant Workers seems to increasing every year, the issue regarding their protection is equally important. The Indonesian government’s existing protection mechanism seems to still lack behind compared to the increasing needs of proper protection steps especially the ones that related to the issue of early detection for HIV/AIDS. The existing regulation of the Head of BNP2TKI No.01/KA/SU/1/2008 is still far from effective at the implementation level. This study examines various healt issues countered by migrant workers before they depart and after they arrive back to Indonesia. To what extent the role of relevant authorities have provide a proper early detection to various health problems experienced by the migrant workers, especially on the issue of HIV/AIDS? It has found that the overall protection mechanism is till far from what is expected, including an early detection mechanism for HIV/AIDS. There is an urgent need on the government side to improve the mechanism and increasing coordination between related departments is a must. Failure to fulfill this could trigger a wider impact as the transmission of HIV/AIDS then may pass on to the family or wider society at the place of origin of the migrant workers. Data collection includes the steps of observation, in-depth interviews, gathering information through informants are individuals who have the knowledge and experience of the problems studied, and the next process is the classification and identification of data based on the theme for the next analysis.